“I Didn't Really Have a Choice”: Qualitative Analysis of Racial-Ethnic Disparities in Diabetes Technology Use Among Young Adults with Type 1 Diabetes - Shivani Agarwal; Gladys Crespo-Ramos; Judith A. Long; Victoria A. Miller (2021)
Background: Racial-ethnic disparities in diabetes technology use are well documented in young adults (YA) with type 1 diabetes (T1D), but modifiable targets for intervention still need to be identified. Our objective was to explore YA perspectives on technology access and support in routine clinical care. Materials and Methods: Participants were YA with T1D of Hispanic or non-Hispanic Black race-ethnicity from pediatric and adult endocrinology clinics in the Bronx, NY. We conducted semistructured individual interviews to explore how health care and personal experiences affected technology use. Interviews were audio-recorded and transcribed for analysis. We used a modified inductive coding approach with two independent coders and iterative coding processes to improve data reliability and validity. Results: We interviewed 40 YA with T1D: mean age 22 years; 62% female; 72% Medicaid insured; 72% Hispanic; 28% non-Hispanic Black; and mean hemoglobin A1C 10.3%. Themes were categorized into potentially exacerbating and alleviating factors of racial-ethnic disparities in technology use. Exacerbating factors included perceptions that providers were gatekeepers of information and prescription access to technology, providers did not employ shared decision making for use, and YA biases against technology were left unaddressed. Alleviating factors included provider optimism and tailoring of technology benefits to YA needs, and adequate Medicaid insurance coverage. Conclusions: Our results reveal potential intervention targets at the provider level to increase technology uptake among underrepresented YA with T1D. Diabetes health care providers need to be aware of inadvertent withholding of information and prescription access to technology. Provider approaches that address YA technology concerns and promote shared decision making help to mitigate racial/ethnic disparities in technology use.